2020
DOI: 10.48550/arxiv.2005.03237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortar-based entropy-stable discontinuous Galerkin methods on non-conforming quadrilateral and hexahedral meshes

Abstract: High-order entropy-stable discontinuous Galerkin (DG) methods for nonlinear conservation laws reproduce a discrete entropy inequality by combining entropy conservative finite volume fluxes with summation-by-parts (SBP) discretization matrices. In the DG context, on tensor product (quadrilateral and hexahedral) elements, SBP matrices are typically constructed by collocating at Lobatto quadrature points. Recent work has extended the construction of entropy-stable DG schemesto collocation at more accurate Gauss q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A simplest example of this idea is shown in Example C.1. The authors found that the technique sketched here is related to the mortar method, see [14,3], the mortar method in SBP context [6,11].…”
Section: C2 Construction From Existing Diagonal Norm Interpolation Op...mentioning
confidence: 96%
See 1 more Smart Citation
“…A simplest example of this idea is shown in Example C.1. The authors found that the technique sketched here is related to the mortar method, see [14,3], the mortar method in SBP context [6,11].…”
Section: C2 Construction From Existing Diagonal Norm Interpolation Op...mentioning
confidence: 96%
“…The boundary condition (4) imposes nonlinear stability to (1) since bounded energy is followed. Indeed, inserting (4) into (6) with zero boundary data…”
mentioning
confidence: 99%
“…A simplest example of this idea is shown in Example A.1. The authors found that the technique sketched here is related to the mortar method, see [12,3], the mortar method in SBP context [6,10]. Example A.1.…”
Section: A2 Construction From Existing Diagonal Norm Interpolation Op...mentioning
confidence: 97%
“…It becomes apparent that the boundary condition (4) imposes nonlinear stability to (1) since bounded energy is followed. Indeed, inserting (4) into (6) with zero boundary data ≡ 0 gives…”
Section: The Continuous Problem To a Viscous Scalar Conservation Lawmentioning
confidence: 99%